The glorious romantics [videorecording] a poetic return to the Regency - Jamson, Marshall; Perry, William (Nebraskan ETV (Great Amwell Production [producer], 1993)
Selections from Byron, Keats and Shelley reveal the individuality and independence of spirit of England's Romantic poets. British actress Jean Marsh complements a wonderful ensemble of actors as this program delights in the words of romance.